2011
DOI: 10.1007/s11605-011-1552-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Operative Recurrence Early After Resection for Crohn’s Disease

Abstract: Earlier recurrence of CD requiring reoperation is associated with specific disease and potentially modifiable operation-related factors such as postoperative complications, i.e., anastomotic leak or intraabdominal abscess. Strategies to reduce recurrence in such patients include the identification of factors that may reduce postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
1
12
0
1
Order By: Relevance
“…The indications for reoperation in our study were penetrating disease, strictures and anastomotic perforation, and bleeding. These were similar to previous studies 15,23 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The indications for reoperation in our study were penetrating disease, strictures and anastomotic perforation, and bleeding. These were similar to previous studies 15,23 .…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, risk factors for reoperation including fistulizing disease, stricture, and operation-related complications can be better visualized at CTE than at IC. 15 Certainly, the small sample size of the present study may not ensure adequate power to compare Rutgeerts score and CTE score in predicting reoperation. Our study has certain limitations.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In other studies, penetrating behavior was a risk factor for postsurgical recurrence [8, 18-20]. However, Khoury et al [21] reported that stricturing behavior was a risk factor for early reoperation. Concerning disease location, several studies demonstrated that the risk of recurrence was highest in ileocolonic CD and lowest in colonic CD [22-24].…”
Section: Discussionmentioning
confidence: 99%
“…The U.S. Centers for Disease Control and Prevention (CDC) Guideline for the Prevention of Surgical Site Infection is the standard of practice for selecting an optimal anti-microbial prophylaxis (AMP) regimen [8]. Empiric broad-spectrum AMP, mainly with first-or secondgeneration cephalosporins, is administered in most cases, in the hope of targeting the most likely pathogens involved in a specific operative procedure.…”
mentioning
confidence: 99%